UK Medical Cannabis Registry: an analysis of clinical outcomes of medicinal cannabis therapy for generalized anxiety disorder. Issue 4 (3rd April 2022) - Ergisi, Mehmet; Erridge, Simon; Harris, Michael; Kawka, Michal; Nimalan, Devaki; Salazar, Oliver; Loupasaki, Katerina; Ali, Rayyan; Holvey, Carl; Coomber, Ross; Platt, Michael; Rucker, James J; et al.
ABSTRACT: Objectives: Anxiety disorders are one of the most common reasons for seeking treatment with cannabis-based medicinal products (CBMPs). Current pharmacological treatments are variable in efficacy and the endocannabinoid system has been identified as a potential therapeutic target. This study aims to detail the changes in health-related quality-of-life (HRQoL) and clinical safety following CBMP therapy for generalized anxiety disorder. Methods: A case series from the UK Medical Cannabis Registry was performed. Primary outcomes included changes from baseline in patient-reported outcome measures (the General Anxiety Disorder Scale (GAD-7), EQ-5D-5L (a measure of health-related quality of life), and Sleep Quality Scale (SQS)) at 1, 3 and 6 months. Statistical significance was defined as p<0.050. Results: Sixty-seven patients were treated for generalized anxiety disorder. Statistically significant improvements were observed in GAD-7, EQ-5D-5L Index Value, EQ5D Visual Analog Scale, and SQS scores at 1, 3 and 6 months (p<0.050). Twenty-five (39.1%) patients reported adverse events during the follow-up period. Conclusion: This study suggests that CBMPs may be associated with improvements in HRQoL outcomes when used as a treatment for generalized anxiety disorder. These findings must be treated with caution considering limitations of study design; however this data may help inform future clinical studies and practice. Plain Language Summary Anxiety disorders are the most prevalent psychiatric illness type in the United Kingdom, with 8.2 million cases reported in 2010. Generalized anxiety disorder (GAD), the most common anxiety disorder, debilitates, and so reduces the quality of life of those who suffer from the condition. The efficacy of current treatments for GAD varies greatly from person-to-person. The endocannabinoid system in the human body is currently attracting a lot of attention in the scientific community as it can be targeted by chemicals in the cannabis plant to produce therapeutic effects in order to treat GAD. There is, however, a lack of studies investigating the effects of medicinal cannabis in GAD, and so this study aims to explore the drug's effect on quality of life in patients suffering from GAD. Sixty-seven patients who attended the Sapphire Clinics for medicinal cannabis treatment for GAD were included in the study. The results from this study highlight that medicinal cannabis may improve generalized anxiety disorder, general health-related quality of life, and sleep-specific outcomes at 1, 3, and 6 months after starting treatment. There was also a low number of severe, disabling, and life-threatening adverse events experienced by patients. Although this study explores the effects of medicinal cannabis in a real clinical setting, the results were not compared to other types of treatment. Future studies with a comparator are therefore needed before concluding the true effects of medicinal cannabis in patients with GAD.